TINDAK TUTUR DIREKTIF GURU PENGGERAK TERHADAP SISWA DALAM PROSES PEMBELAJARAN DI SMPN 4 TAKALAR - Rahmayanti; Muhammad Saleh; Tuti Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe 1) the use of directive speech acts by lead teachers towards pupils during the learning process at SMPN 4 Takalar. This study was conducted with two teachers, namely the Indonesian language lead teacher and the Civic Education teacher. Data collection techniques included observation, recording, listening, and note-taking. Data analysis employed three stages comprising data reduction, data presentation, and drawing conclusions. Data verification was carried out through expert and source triangulation. The research results indicate that: 1) the functions of directive speech acts used by the lead teacher towards students in the learning process at SMPN 4 Takalar revealed 10 functions of directive speech acts, with the questioning function being the most frequently observed. Meanwhile, in this study, the following functions were not found: requesting, pressuring, praying, inviting, dictating, stipulating, directing, approving, restricting, praying, desiring, suggesting, reminding, and advising.